Orality, Ossian and translation - Bär, Gerald (2021)
Epics, ballads, prose tales, ritual and lyric songs, as genres, existed orally before writing was invented. Serious debate about them, at least in modern Western culture, may be said to have begun with James Macpherson and Thomas Percy. Considering the ongoing debate on orality and authenticity in the case of Ossian, this book includes ground-breaking, previously published essays which provide essential information relating to orality, Ossian and translation, but have been frequently overlooked. Its contributions focus on the aspects of authenticity, transmediation, popular poetry and music, examining Scottish, German, Portuguese, Brazilian, African, American Indian, Indian and Chinese literatures.